Quantitative determination of traces of free gossypol in fats, oils, and fatty acids by paper chromatography - Schramm, Guenter; Benedict, James H. (Journal of the American Oil Chemists' Society, 1958)
Summary A quantitative method for the determination of traces of free gossypol in oils and fatty acids was developed. The method is based on the concentration of gossypol by extraction and quantitative paper chromatography of the extract. The method is specific for free gossypol and is not subject to interferences. The new method is both accurate and reproducible. The lower limit of detection is 10 p.p.m. The method is intended primarily for p.p.m. levels but is suitable for all concentrations. With slight modifications the method is applicable to meals.